1999
DOI: 10.1177/107769909907600409
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intermedia and Newspaper Competition on Advertising Linage in Daily Newspapers

Abstract: This exploratory study of forty dailies found a negative relationship between the number of radio and television stations and daily newspaper ROP advertising. A weaker relationship was found between number of radio and television stations and total advertising linage in daily newspapers. The markets used here varied greatly in competition's impact on linage. It appears intermedia advertising is monopolistically competitive with some media being better at some types of advertising than others. These results hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A study by Shaver and Lacy (1999) indicated that there is a negative relationship between competition among firms and the advertising success. This indicates that highly competitive firms are usually more successful in advertising (Amiri Aghdaie et al, 2012).…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…A study by Shaver and Lacy (1999) indicated that there is a negative relationship between competition among firms and the advertising success. This indicates that highly competitive firms are usually more successful in advertising (Amiri Aghdaie et al, 2012).…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…Since that time, the effectiveness of cable television's entrance into the marketplace (Dimmick, Patterson, & Albarran, 1992), the video industry (Albarran & Dimmick, 1993; Dimmick, 1997), media preferences (Dimmick, 1993), new media ventures (Dimmick & Wallschlaeger, 1986), as well as telephone and email use (Dimmick, Kline, & Stafford, 2000) have been studied. Other recent applications by other authors, building further on niche theory and its application to both new and old media, include the impact of intermedia and newspaper competition on advertising sales (Shaver & Lacy, 1999), the Web as a new marketing channel in comparison to catalogs and retail stores (Li, 2000), and the displacement of old media by online media within the home (Kayany & Yelsma, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Monitoring competitors also has a positive influence on a media innovation's success (Habann, 2010). Numerous studies focus on the influence of competition on content and advertising (e.g., Becker, Hollifield, Jacobsson, Jacobsson, & Vlad, 2009;Coulson & Lacy, 1996;Lacy, 1987;Shaver & Lacy, 1999). Research also finds that media outlets respond to competition, for instance, through release strategies, product differentiation, and increasing expenditures (Krider & Weinberg, 1998;Lacy & Martin, 2004;Lee & Han, 2006;Shrikhande, 2001).…”
Section: Media Industry and Startupsmentioning
confidence: 99%